Construcciones del Sentido de Pertenencia al Espacio Público Comunitario en niños, niñas y jóvenes entre 5 a 16 años, del barrio San José 1, de la Parroquia Cutuglagua, en el año 2016 - Santander Vaca, Diego Bladimir (2017)
In this written work the research on "Appropriation of Public Spaces in children / as and San Jose neighborhood youth 1 Cutuglagua parish", conducted in 2015-2016 unfolds. As a first step a social diagnosis was made in the sector, to meet the most pressing problems of the population, subsequently recreational and socialization workshops that served as observation groups to develop the research work were created. Reference is also made to subcategories like "action and construction of places", "symbolic space" and "social identity" terms that give us a contextualization of the main characteristics of the problems of this social group, such as lack of streets of the neighborhood, who are the authorities of the community, who lives in the surrounding area and the little appropriation of existing public spaces, thus reaching conclusions and recommendations for community work.